Iron nutrition status in 4 to 14 year-old children living in a marginal urban section in Lima - Fernández, Alicia (2007)
Objective: To determine the iron nutrition status in 4 to 14 yearold children. Design: Descriptive, observational, transversal and prospective study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: Four to fourteen year-old children. Interventions: We studied 349 children 4 to 14 year-old, 170 males and 179 females, at San Genaro Health Center, Chorrillos, from September 2001 through August 2002. Main outcome measures: Iron nutritional status. Results: From these children, 68,8% (240) did not present alteration in iron nutrition status (INS), compared with 31,2% who presented this alteration. From the 109 children with iron nutrition status alteration, 68,8% (75) were stage I or latent depletion (ferritine <20 ng/mL); 22,9% (25) were stage II or iron deficient (serum iron <60 ug/dL and iron total capacity of fixation >400 ug/dL), and 8,3% (9) were in stage III with iron deficient anemia (hemoglobin <11,5 g/100 mL for children less than 11 year-old and <12 g/100mL for children 12 to 14 year-old, hematocrit <34% for children less than 11 year-old and <36% for children 12 to 14 year-old, median corpuscupar volume < 80 fl and median corpuscular hemoglobin <27 pg). Conclusions: The high percentages of children with alteration of the iron nutrition status stage I identifies a population with iron deficiency anemia risk. We recommend that iron deficiency studies be applied only to children in stage I, in order to institute citizen participation public policies and establish alliances with other sectors (education), for child nutrition promotion.